A Critical Discourse Analysis: Framing Justice through Netflix Documentary “Ice Cold; Murder, Coffee, and Jessica Wongso” - Bethellionie Wahyudi (Jurnal Hasil Penelitian dan Pengembangan (JHPP), 2025)
Nowadays, framing of Indonesia's criminal justice gains critical attention in discourse discipline, reckoning the emergence of a documentary film by Netflix entitled Ice Cold; Murder, Coffee, & Jessica Wongso, resulting in mass reactions toward how Indonesia creates justice. Consequently, this study employs qualitative critical discourse analysis, aiming to investigate the current portrayal of criminal justice in Indonesia, also seek a societal understanding toward the issue by addressing a couple of research questions, Thus, the documentary exposes the Indonesia justice system being illustrated in negativism, following the legal power relation and gender based portrait, All together, it leads to voice the pros and cons toward the case that had been closed through Indonesian supreme court decision with the number 498/K/PID/2017. Further study that adopts discursive strategies in visualizing justice in the documentary should be conducted.